Visual aids for support teachers in learning - Sirait, Debora; Simbolon, Lolyta Damora; Purba, Switamy Angnitha; Manulang, Ady Frenly (Talenta Publisher, 2020)
Learning media in general is a tool for teaching and learning. Everything that can be used to stimulate the thoughts, feelings, attention and abilities or skills of students so as to encourage the learning process. This limitation is quite broad and includes the understanding of resources, environment, people and methods used for learning / training purposes. Barriers to the use of teaching aids in supporting student interest in learning, obstacles include: conditioning students' attention to learning with teaching aids, teacher learning methods that tend to be less varied so that students are less enthusiastic in learning if the teacher is monotonous, the teaching aids available in schools are incomplete, making teaching aids in accordance with the material and student input is difficult, the minimum time to prepare learning with teaching aids.